Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)